KENDALA YANG DIHADAPI HAKIM DALAM PELAKSANAAN MEDIASI PERCERAIAN DI PENGADILAN AGAMA SRAGEN - Ari Prasetyo; Agus Rianto (Universitas Sebelas Maret, 2013)
This study aims to know clearly about divorce mediation implementation in the Religious Sragen, and to know what the constraints faced by judges for divorce mediation in Court of Religious Sragen and how the best solution. This study uses empirical legal research is descriptive qualitative approach. Source of data derived from the primary data source is the interview and observations by following a mediation session for the three cases. Secondary data sources derived from literature, scientific books, papers / scholars scientific results, and documents relating to the object of research. From the results of research and discussion, it is concluded that the implementation of divorce mediation in the Court of Religious Sragen is as follows: pre-mediation, mediation, post-mediation. Constraints faced in the implementation of the mediation judge among others the number of judges that bit, there are two views that may occur related to the absence of the parties or a party in the first trial when it will be held at mediation, mediation success difficult because there are also non-material factors in divorce, the cost of the profession meditor than judges and limit the fees that are not clear. Likewise with solutions related to the implementation of mediation, is still derived from the fourth constraint. Keywords: The Court of Religious Sragen, divorce, divorce mediation, judges constraints and solutions.